Karakteristik Keberhasilan Kehamilan Pasien Yang Menjalani Bayi Tabung Dengan Protokol Panjang Di Klinik Bayi Tabung Rumah Sakit Umum Pusat Sanglah Tahun 2014-2017 - Hariantha Putra, Putu Surya Pradipta; Manuaba, Ida Bagus Gede Fajar; Jaya Kusuma, Anak Agung; Wijaya Surya, I Gede Harry (E-Jurnal Medika Udayana, 2023)
Introduction : Globally there are estimated cases of infertility in 8%-10% of couples, if from the global picture of the population then about 50-80 million couples (1 in 7 couples) or about 2 million new infertile pairs each year and this number continues to increase. In Vitro Fertilization (IVF) can be a solution for infertile patients. There are two IVF programs, namely with short protocols and long protocols, each protocol has benefits and limitations, The long protocol was the most widely used protocol prior to the introduction of GnRH antagonists (short protocols) in IVF centers around the world, but high cost constraints leads change over to the short protocol method. In its journey, the average success rate of IVF cycles ranges from 25-30%, while in Indonesia it is 29% for one cycle of long protocol. Thus, this study aims to determine characteristics of success rate patients undergoing ivf with long protocol at ivf clinic Sanglah General Hospital. Methods: This research is a descriptive study using medical record data and the sampling technique is saturation sampling. The data obtained according to the inclusion and exclusion criteria were 4 data which were analyzed descriptively for each case. Result: This study shows that out of 87 cases underwent the ivf program at RSUP Sanglah Clinic only 4 cases who underwent IVF with the long protocol, only 1 case was success, the age of the male partner was 35 years old and the female partner was 35 years old with primary infertile status for 4 years, had a total of 12 oocytes and 4 embryos and appropriate for the long protocol criteria. IVF with levels of ?-hCG 204.1 mIU / ml and get Geneli's pregnancy .Conclusion: During the 2014-2017 period, only 4 cases of patients undergoing IVF with the long protocol method were found, 3 cases with ?-hCG <50,2 did not get live birth while 1 case with ?-hCG> 50,2 had a viable pregnancy.